Interactive effects of elevated carbon dioxide and nitrogen availability on fruit quality of cucumber (Cucumis sativus L.) - Jin-long DONG; Xun LI; Gruda Nazim; Zeng-qiang DUAN (Journal of Integrative Agriculture, 2018)
Elevated CO2 and high N promote the yield of vegetables interactively, whilst their interactive effects on fruit quality of cucumber (Cucumis sativus L.) are unclear. We studied the effects of three CO2 concentrations (400 μmol mol−1 (ambient), 625 μmol mol−1 (moderate) and 1 200 μmol mol−1 (high)) and nitrate levels (2 mmol L−1 (low), 7 mmol L−1 (moderate) and 14 mmol L−1 (high)) on fruit quality of cucumber in open top chambers. Compared with ambient CO2, high CO2 increased the concentrations of fructose and glucose in fruits and maintained the titratable acidity, resulting in the greater ratio of sugar to acid in moderate N, whilst it had no significant effects on these parameters in high N. Moderate and high CO2 had no significant effect on starch concentration and decreased dietary fiber concentration by 13 and 18%, nitrate by 31 and 84% and crude protein by 19 and 20% averagely, without interactions with N levels. The decreases in amino acids under high CO2 were similar, ranging from 10–18%, except for tyrosine (50%). High CO2 also increased the concentrations of P, K, Ca and Mg but decreased the concentrations of Fe and Zn in low N, whilst high CO2 maintained the concentrations of P, K, Ca, Mg, Fe, Mn, Cu and Zn in moderate and high N. In conclusion, high CO2 and moderate N availability can be the best combination for improving the fruit quality of cucumber. The fruit enlargement, carbon transformation and N assimilation are probably the main processes affecting fruit quality under CO2 enrichment.